2018
DOI: 10.1016/j.anorl.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of allergy on phenotypic and endotypic profiles of nasal polyposis

Abstract: The present results suggest that allergy is not directly involved in the clinical expression and specific inflammatory pathways of CRSwNP. New therapies target inflammation signaling pathways, and identifying accurate blood and tissue biomarkers will be the line of research most likely to improve treatment of CRSwNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The variability in the levels of activation of these inflammatory pathways was associated with the presence of clinical characteristics such as nasal polyposis or comorbid asthma . Clustering of CRS patients based on the inflammatory signatures observed in the nasal mucus, which correlates with clinical disease characteristics, has also been reported …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The variability in the levels of activation of these inflammatory pathways was associated with the presence of clinical characteristics such as nasal polyposis or comorbid asthma . Clustering of CRS patients based on the inflammatory signatures observed in the nasal mucus, which correlates with clinical disease characteristics, has also been reported …”
Section: Discussionmentioning
confidence: 92%
“…30 Clustering of CRS patients based on the inflammatory signatures observed in the nasal mucus, which correlates with clinical disease characteristics, has also been reported. 34,35 Interestingly, studies have shown diversity in association between inflammatory signatures and CRS disease characteristics based on geography and racial backgrounds. [36][37][38] For example, in Europe, North America and Oceania CRSwNP is associated with a predominantly Th2 inflammatory signature in the sinonasal mucosa in contrast to a mixed Th1/Th2/Th17 cytokine profile with generally lower levels Th2 inflammation in Asian CRSwNP patients.…”
Section: Crs Endotypesmentioning
confidence: 99%
“…They found that there is no difference between the mentioned two groups. In fact, the atopic status has no effect on the levels of IgA in both serum and nasal secretions (17). However, an old study reported that local IgA production occurred in both allergic and non-allergic CRSwNP patients, resulting in degranulation of cytotoxic proteins from eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…8 According to this system, a higher score correlates with a more severe disease (six regions on each side, scored 0-2). 7 This score was also subclassified into mild (1)(2)(3)(4)(5)(6)(7)(8), moderate (9-16) and severe (17)(18)(19)(20)(21)(22)(23)(24). A complete blood cell count with differential cell count was performed in all patients and eosinophil parameters were collected.…”
Section: Methodsmentioning
confidence: 99%
“…All patients underwent preoperative CT scan. The mean Lund-Mackay score was 12.7±4.7 and 21% of study population had a severe paranasal sinus obliteration (score [17][18][19][20][21][22][23][24]. A Spearman's correlation was performed to determine the relationship between the Lindholt and Lund-Mackay score system.…”
Section: Patient Characteristicsmentioning
confidence: 99%